NOX2 and NOX4 expression in monocytes and macrophages-extracellular vesicles in signalling and therapeutics - Rathi, Deepak; Rossi, Claudio; Pospíšil, Pavel; Ramalingam Manoharan, Renuka; Talarico, Luigi; Magnani, Agnese; Prasad, Ankush (Frontiers in Cell and Developmental Biology, 2024)
Extracellular vesicles (EVs) are a type of cytoplasmic vesicles secreted by a variety of cells. EVs originating from cells have been known to participate in cell communication, antigen presentation, immune cell activation, tolerance induction, etc. These EVs can also carry the active form of Nicotinamide Adenine Dinucleotide Phosphate Oxidase Hydrogen (NADPH) oxidase, which is very essential for the production of reactive oxygen species (ROS) and that can then modulate processes such as cell regeneration. The aim of this study is to characterize the EVs isolated from U-937 and THP-1 cells, identify the NADPH oxidase (NOX) isoforms, and to determine whether EVs can modulate NOX4 and NOX2 in monocytes and macrophages. In our study, isolated EVs of U-937 were characterized using dynamic light scattering (DLS) spectroscopy and immunoblotting. The results showed that the exogenous addition of differentiation agents [either phorbol 12-myristate 13-acetate (PMA) or ascorbic acid] or the supplementation of EVs used in the study did not cause any stress leading to alterations in cell proliferation and viability. In cells co-cultured with EVs for 72 h, strong suppression of NOX4 and NOX2 is evident when monocytes transform into macrophagic cells. We also observed lower levels of oxidative stress measured using immunoblotting and electron paramagnetic resonance spectroscopy under the EVs co-cultured condition, which also indicates that EVs might contribute significantly by acting as an antioxidant source, which agrees with previous studies that hypothesized the role of EVs in therapeutics. Therefore, our results provide evidence for NOX regulation by EVs in addition to its role as an antioxidant cargo.